Living Kidney Donation in Spain, A Global Strategy to Increase this Modality of Transplantation. (July 2018) - Valentin, Maria; Mahillo, Beatriz B; Martinez, Itziar I; Garcia, Marta M; Ormeño, Miriam M; Calderari, Elena E; Coll, Elisabeth E; Domínguez-Gil, Beatriz B
Abstract : Objective: To describe the impact of a strategy implemented to broaden living kidney donation over the last eleven years. Methods: Between January 2005 and December 2016, the Spanish National Transplant Organization together with the Network of kidney transplants teams undertook the following measures: Training: (living kidney donation courses targeted to health-care professionals); promotion through public campaigns, in collaboration with patient's associations, and a specific website developed and maintained to inform general population on living donation; Clinical guidelines were developed by the ONT in cooperation with the Spanish Society of Nephrology; the implementation of the Spanish living kidney donation registry (in 2010); strategies to overcome donor-recipient incompatibility as the National Kidney Exchange program (in 2009); a protocol for the work up of altruistic donors (in 2010). Living donor activity has been analysed. Results: Living kidney donation activity has increased from 87 to 343 (294% increment), the last accounting for 7.4 pmp. 142 kidney paired transplants have been performed. For the same period, 10 altruistic donors have triggered 32 transplants. However, 4321 patients still remained on the waiting list at the end of 2016. Living donation was different among regions. Thus, in 2016 Cataluña, Galicia and País Vasco reached 18.35, 10.33 and 9.63 living donor kidney transplants pmp respectively. Conclusion: The strategy to increase living donation has been successful in some regions with low increase in others. Benchmarking procedures should be implemented to search for specific measures that have contributed to success.